A Retrospective Study: The Profile of New Gonorrhoeae Patients - Dewi Puspitorini; Hans Lumintang (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Incidence of sexually transmitted infections are still high, gonorrhoeae is one of them. Statistic data on 2008 revealed 25.4 million cases of gonorrhoeae in Southeast Asia. On condition of gonorrhea is not treated adequately can lead to the expansion of the disease, resulting in complications such as pelvic inflammatory disease (PID). Purpose: To evaluate profile of new gonorrhoeae patients. Methods: Retrospective study of profile of new gonorrhoe patients in Sexually Transmitted Infections Division in Dermatovenereology Outpatient Clinic between the year 2010-2012. Results: There were 135 gonorrhoeae patients, the majority were men 125 patients (92.6%) much more than women 10 patients (7.4%) , mostly of the age group 25-44 years old 84 patients (62.2%), and mostly were single 74 patients (54.8%) majority of symptom is dysuria 66 patients (48.8%). Local status from examination with the highest result was erythem and oedem of orificium urethra externum 88 patients (65.2%). The majority of sexual partner is boyfriend or girldfriend 56 patients (41.5%). Laboratory examination showed diplococcus negative gram 135 patients (100%). The most used therapy was combination of doxycycline and cefixime (90 patients). Conclusion: Gonorrhoeae is a sexually transmitted infection that occur mostly on productive-age patients. Right management dan education to the patients are needed for therapy and prevention of the disease.